Dėl kalbėjimo veiksmažodžių leksinės semantinės grupės - Vasiliauskienė, D. (Kalbotyra, 1979)
The present article is a review of the existing opinions on the status of the different semantic groups of verbs in the lexical system of language, with particular reference to VERBA DICENDI in Lithuanian and English. Factors relevant to the identification of VERBA DICENDI in the two languages are considered and the relations of these verbs to the other semantic groups of verbs are discussed.